2019
DOI: 10.1155/2019/6328329
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Machine Learning-Based Quantitative Texture Analysis in Differentiating Benign and Malignant Thyroid Nodules

Abstract: Aim The aim of this study is to evaluate the diagnostic value of machine learning- (ML-) based quantitative texture analysis in the differentiation of benign and malignant thyroid nodules. Materials and methods A sum of 306 quantitative textural features of 235 thyroid nodules (102 malignant, 43.4%; 133 benign, 56.4%) of a total of 198 patients were investigated using the random forest ML classifier. Feature selection and dimension reduction were conducted using reproducibility testing and a wrapper method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…As our sample number was lower compared with that in common industrial cases, 2 clinical indices and 14 CT features were selected; 16 indicators were included in the statistical analysis according to prior clinical knowledge for prediction. ML has been shown to have a great advantage in tumor diagnosis as well as prognosis and recurrence prediction, with an increasing number of reports involving hepatic carcinoma (13), thyroid nodules (14), renal tumors (15) and colon cancer (16), among others. Previous studies have demonstrated that ML-based texture analysis has diagnostic accuracy ranging from 98.3 to 100% for neoplastic lesions of the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…As our sample number was lower compared with that in common industrial cases, 2 clinical indices and 14 CT features were selected; 16 indicators were included in the statistical analysis according to prior clinical knowledge for prediction. ML has been shown to have a great advantage in tumor diagnosis as well as prognosis and recurrence prediction, with an increasing number of reports involving hepatic carcinoma (13), thyroid nodules (14), renal tumors (15) and colon cancer (16), among others. Previous studies have demonstrated that ML-based texture analysis has diagnostic accuracy ranging from 98.3 to 100% for neoplastic lesions of the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that the histogram feature was the most important parameter in classification, and both SVM (94.64%) and random forests (92.42%) achieved high accuracy. Colakoglu et al [ 85 ] attempted to differentiate benign and malignant thyroid nodules using texture analysis and random forest model construction. After testing the reproducibility of all texture features, they finally screened seven texture features from ultrasound images, including one histogram (HistPerc 99), one HOG (HogO8b2), four GRLMs (GrlmHRLNonUni, GrlmHMGLevNonUni, GrlmNRLNonUni, and GrlmZRLNonUni), and one GLCM (GlcmZ3AngScMom), in a random forest model.…”
Section: Radiomics In Thyroid Cancer and Nodule Classificationmentioning
confidence: 99%
“…The authors in Reference 14 applied one ML technique which is Random Forrest Classifier (RFC) algorithm to perform classification of the thyroid nodules. Similarly, the study in Reference 15 run RFC and present the important classifiers in the textual dataset. The study in Reference 16 developed and validated a ML based radiomics model for evaluating immunohistochemical characteristics in patients with suspected thyroid nodules.…”
Section: Related Work and Motivationmentioning
confidence: 99%